miR-137 inhibits melanoma cell proliferation through downregulation of GLO1 - Lv, Na; Hao, Shuai; Luo, Chonglin; Abukiwan, Alia; Hao, Ying; Gai, Fei; Huang, Weiwei; Huang, Lingyun; Xiao, Xueyuan; Eichmüller, Stefan B.; He, Dacheng (Science China. Life sciences, 2018)
Late-stage melanoma is refractory to current therapies. MicroRNAs (miRNAs) can modulate many physiological and pathological processes of melanoma. Studies have demonstrated that miR-137 acts as a tumor suppressor by inhibiting the proliferation of melanoma cells through targeting multiple mRNAs. The glyoxalase system member glyoxalase 1 (GLO1) is the principal scavenging enzyme of methylglyoxal (MG), a toxic byproduct of glycolysis. Using 35S in vivo/vitro labelling analysis for dynamic proteomics (SiLAD), we found that miR-137 downregulated the expression of GLO1 in melanoma cells. Bioinformatics analysis predicted that GLO1 is a direct target of miR-137. This was validated by dual luciferase reporter assay. Quantitative RT-PCR (qRT-PCR) and western blot analysis indicated that miR-137 could decrease endogenous GLO1 expression. Furthermore, siRNA targeting of GLO1 mimicked inhibition of melanoma cell proliferation caused by miR-137 overexpression. Re-expression of GLO1 was able to restore miR-137-mediated suppression of melanoma cell proliferation. Therefore, these results suggest that miR-137 inhibits the proliferation of melanoma cells by targeting GLO1.